INDIAN PULSES- PROSPECTS OF ACHIEVING SELF-SUFFICIENCY - Raghunadha Reddy, G., Govindaraju, K.V., Pravallika, K.V. S.D., Ramesh Naik, S and Sirisha, K.J.V.K. (The Journal of Research ANGRAU, 2023)
The trend in area, production, and yield of major pulses in India through growth rate and instability analysis from 2000-01 to 2021-22 to reveal the position with an objective to support th way forward to achieve self-sufficiency. The growth rates were calculated by fitting the semi-log linear growth function, and instability was analyzed with the help of Coppock’s Instability Index (CII) for the total pulses of Indiaalong with spatial and temporal patterns of area, production, and yield among major pulses. The results have shown a significantly positive trend in area, production, and yield of major pulses over the period of time. The compound annual growth in area and production showed positive but decreased trends after 2010–11 compared to earlier period. However, the yield growth rate was found higher than the growth rate in area, implying that area allocation for pulses is increasing marginally after 2010-11 while improvement in yield noticed. The main factors responsible include improvements in technologies and government support through schemes such as NFSM. In case of stability, yield factor has comparatively larger variability in sub-periods I and II, which are 0.42 and.0.44, respectively, as in production, whereas, instability is a bit lower in the case of area under cultivation.